39. EFFECT OF “BO DUONG HOAN NGU THANG” IN COMBINATION WITH ACUPRESSURE MASSAGE IN THE TREATMENT OF COMPLICATIONS OF PERIPHERAL NERVES OF THE LOWER EXTREMITIES IN PATIENTS WITH TYPE 2 DIABETES (Vietnam Journal of Community Medicine, 2024)
Background: Complications of diabetes are very diverse, with peripheral neuropathy of the lowerextremities accounting for a high rate. “Bo duong hoan ngu thang” combined with accupressuremassage contribute effectiveness in treatment, but it needs to be proven by research.Objectives: Evaluating the effect of Bo duong hoan ngu thang combined with accupressure massageto treat peripheral nerve complications of the lower extremities in patients with type 2 diabetes, andat the same time to monitor effects unwanted.Subjects and methods: Clinical intervention compared before, after treatment and control in 60patients randomly devided into 2 groups. The study group used "Bo duong hoan ngu thang" combinedwith acupressure massage and Thioctic Acid. The control group used Thioctic Acid. The study periodwas 21 days. Criteria to evaluate the results of functional and physical symptoms, traditionalmedicine, according to the VAS, UKST, SF-36 scales and the blood Glucose index.Results: The study group improved the functional, physical symptoms and traditional medicinebetter than the control group (p
Keywords: Lower extremity peripheral neuropathy, Bo duong hoan ngu thang.